Thin-layer chromatography of DNS amino acids derivatives in systems with silica gel and silanized silica gel plates - Chomicki Adam; Dzido Tadeusz H. (Current Issues in Pharmacy and Medical Sciences, 2022)
Investigations into separation selectivity of High-Performance Thin-layer chromatography (HPTLC) of dansyl (DNS) derivatives of amino acids in silica gel (Silica gel 60 F254s plates) and silanized silica gel (RP-18 W plates) systems are presented. The results have been obtained for mobile phases containing different concentrations of acetonitrile (ACN) in formic acid (FA) water solution (final concentration of FA in the mobile phase was equal to 265 mmol/dm3). The data obtained show differences in separation selectivity of the solutes between employment of HPTLC silica gel and RP-18 W systems.